Prevalence and Antifungal Susceptibility of Pathogenic Yeasts in China: A 10-Year Retrospective Study in a Teaching Hospital - Song, Yinggai; Chen, Xianlian; Yan, Yan; Wan, Zhe; Liu, Wei; Li, Ruoyu (Frontiers in Microbiology, 2020)
To determine the dynamic changes of pathogenic yeasts prevalence and antifungal susceptibility pattern in tertiary hospitals in China, we analyzed 527 yeast isolates preserved in the Research Center for Medical Mycology at Peking University, Beijing, China between Jan 2010 and Dec 2019, and correctly identified 19 yeast species by MALDI-TOF MS and ribosomal DNA sequencing. Antifungal susceptibility testing was performed following a Sensititre YeastOne colorimetric microdilution panel with clinically available nine antifungals. The CLSI-approved standard M27-A3 (S4) and newly revised clinical breakpoints or species-specific and method specific epidemiological cut-off values were used for the interpretation of susceptibility test data. In this study, although Candida albicans was the predominant single species, non-C. albicans species constituted >50% of isolates in 6 out of 10 years and more rare species were present in the recent 5 years. Non-C. albicans species identified most frequently were Candida parapsilosis sensu stricto, Candida tropicalis, and Candida glabrata. The prevalence of fluconazole and voriconazole resistance in C. parapsilosis sensu stricto population was <3%, but C. tropicalis exhibited decreased susceptibility to fluconazole 42 (57.5%) and voriconazole 31 (42.5%), and 22 (30.1%) C. tropicalis isolates exhibited wild-type MICs to posaconazole. Furthermore, fluconazole and voriconazole cross-resistance prevalence in C. tropicalis was 19 (26.1%). The overall prevalence of fluconazole resistance in the C. glabrata population was 14 (26.9%), and prevalence of isolates exhibiting voriconazole non-wild-type MICs was 33 (63.5%). High-level echinocandin resistance was mainly observed in C. glabrata, and the prevalence of isolates resistance to anidulafungin, micafungin, and caspofungin were 5 (9.6%), 5 (9.6%), and 4 (7.7%), respectively. Moreover, one C. glabrata isolate showed multidrug resistant to azoles, echinocandins and flucytosine. Overall, the ten-year surveillance study showed the increasing prevalence of non- C. albicans species over time; the emergence of azole resistance in C. tropicalis and multidrug resistance in C. glabrata over the years reinforced the need for epidemiological surveillance and monitoring.